Muscle growth of triploid Atlantic cod juveniles (Gadus morhua) - Vargas, Cecilia Campos; Peruzzi, Stefano; Palihawadana, Anjana; Ottesen, Oddvar; Hagen, Ørjan (Aquaculture Research, 2015)
Accepted manuscript version. Published version at http://doi.org/10.1111/are.12879 . This study has investigated the muscle growth of diploid and triploid Atlantic cod (Gadus morhua) juveniles raised in replicate tanks over a period of 29 weeks and analysed at three sampling points (February, June and September). Data for weight, length, condition factor (K), muscle ﬁbre growth and myogenic progenitor cells (MPCs) number were collected and results were analysed in relation to body growth and ploidy status. Diploids were signiﬁcantly heavier than triploids throughout the trial (~10–20%) and had K in June and September samplings. Over the whole period, the rate of muscle ﬁbres’ recruitment was 318 ﬁbres per day and 252 ﬁbres per day for diploid and triploid cod respectively. The larger body weight of diploids resulted in a total num- ber of fast ﬁbre number of 114 979 compared to 91 086 in triploids. The average diameter of the 2.5% of the smallest ﬁbres (2.5th percentile) was higher in diploids than triploids at the start of the trial, with a reversed picture for the aver- age of the upper 2.5% (97.5th percentile) at the end of the trial. The probability density function of the estimated muscle ﬁbre diameters showed similar ﬁbre size distribution between size- matched diploids and triploids at all sample points. The peak ﬁbre diameter was approxi- mately 25 lm in February and increased to approximately 50 lm in June and September, irrespectively of ploidy. Pax 7 were used as molecular markers for MPCs. A positive correla- tion between Pax 7+ cells and total body length was observed only among triploid ﬁsh at the onset of the experiment.